Analisis Pelanggaran Hukum pada Kasus Pencabutan Izin Usaha Bank Pengkreditan Rakyat Persada Guna Pasuruan - Muhammad Arsyadani Rohman; Nadya Putri Pramesti; Nia Rizkita Nurfitri; Emma Yunika Puspasari (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
More and more BPRs have had their operational permits revoked by the OJK. The revocation of a BPR license is due to the bank's unhealthy financial condition, which has the potential to threaten the banking system and harm various parties. Therefore, the bank must have its business license revoked with several previously determined considerations. One of the BPRs whose business license was revoked was BPR Persada Guna Pasuruan. This research aims to analyze the forms of legal violations in the case of revocation of BPR Persada Guna's business license and find out the follow-up given by the authorities in the case of BPR Persada Guna Pasuruan. This research uses a normative juridical approach. The research results show that the forms of legal violations include credit violations, capital insufficiency, and violations of bank governance. Meanwhile, the follow-up provided is through the Decree of the Members of the Board of Commissioners of the Financial Services Authority Number KEP-84/D.03/2023 dated 4 December 2023 regarding the Revocation of the Business License of PT Bank Kredit Kredit Rakyat Persada Guna.